Effect of using educational videos in teaching web design on academic achievement of students - Alibo, Tuotamunonengi Kate; Tolowodun, Ben Charles (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
This study sought to ascertain the effect of using educational videos in teaching web design on the academic achievement of students. Quasi-experimental research design was adopted for the study and the study population comprised 351 undergraduates offering Website Design in two tertiary Universities in Rivers State. A purposive sampling technique was used to draw the sample size of 162 fourth-year students from the two universities. The instrument for data collection was a Web Design Achievement Test (WDAT) which the researchers developed and was validated by three research experts. The reliability of the instrument was determined using Kuder-Richardson 21 (KR-21) with a reliability index of .83. Mean and standard deviation were used for answering the research questions while Analysis of Covariance was used to test the null hypotheses at a significance level of 0.05. The findings of the study revealed that students who were exposed to educational videos outperformed more than their colleagues who were instructed with the conventional teaching method. Based on the findings, the study recommends that Educators should integrate educational videos into their teaching practices to enrich learning experiences and improve student achievement.